2019
DOI: 10.1016/j.scitotenv.2019.134066
|View full text |Cite
|
Sign up to set email alerts
|

Use of dual element isotope analysis and microcosm studies to determine the origin and potential anaerobic biodegradation of dichloromethane in two multi-contaminated aquifers

Abstract: Many aquifers around the world are impacted by toxic chlorinated methanes derived from industrial processes due to accidental spills. Frequently, these contaminants co-occur with chlorinated ethenes and/or chlorinated benzenes in groundwater, forming complex mixtures that become very difficult to remediate. In this study, a multi-method approach was used to provide lines of evidence of natural attenuation processes and potential setbacks in the implementation of bioremediation strategies in multi-contaminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 67 publications
1
3
1
Order By: Relevance
“…Our findings may also contribute to a better understanding of the attenuation of halogenated POPs at sites contaminated with multiple groups of organohalide pollutants. Multiple organohalide compounds are frequently found at contaminated sites (e.g., soil and sediment adjacent to e-waste recycling facilities), , and such co-contamination is conventionally thought to impair bioremediation efforts. , However, in the current study, we found that some organohalide pollutants (i.e., penta-BDEs and PCE in the case of D. mccartyi strain MB) could act as growth-supporting substrates to stimulate cell growth for attenuation of the more persistent organohalide pollutants (i.e., PCBs) that do not support the growth of the given OHRB.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings may also contribute to a better understanding of the attenuation of halogenated POPs at sites contaminated with multiple groups of organohalide pollutants. Multiple organohalide compounds are frequently found at contaminated sites (e.g., soil and sediment adjacent to e-waste recycling facilities), , and such co-contamination is conventionally thought to impair bioremediation efforts. , However, in the current study, we found that some organohalide pollutants (i.e., penta-BDEs and PCE in the case of D. mccartyi strain MB) could act as growth-supporting substrates to stimulate cell growth for attenuation of the more persistent organohalide pollutants (i.e., PCBs) that do not support the growth of the given OHRB.…”
Section: Discussionsupporting
confidence: 90%
“…Multiple organohalide compounds are frequently found at contaminated sites (e.g., soil and sediment adjacent to e-waste recycling facilities), 31,63 and such co-contamination is conventionally thought to impair bioremediation efforts. 52,64 However, in the current study, we found that some organohalide pollutants (i.e., penta-BDEs and PCE in the case of D. mccartyi strain MB) could act as growth-supporting substrates to stimulate cell growth for attenuation of the more persistent organohalide pollutants (i.e., PCBs) that do not support the growth of the given OHRB. It should be noted, however, that the co-metabolic dechlorination stimulated by metabolically dehalogenated substrates in a specific strain most likely occurred because dehalogenation of each organohalide was attributed to the same RDase, MbrA, and may not be a general feature of OHRB that employ separate RDases to dehalogenate different organohalides.…”
Section: ■ Discussioncontrasting
confidence: 68%
“…The present study ranked chloroform as the most detrimental cocontaminant inhibiting microbial reductive dechlorination of DCEs by Dehalococcoides -containing consortia, followed by 1,1,1-TCA and 1,1,2-TCA. Notably, both chloroform and 1,1,1-TCA demonstrated evident inhibitory effects on DCE dechlorination at concentrations ≥ 5 μmol/L, which is within the environmental detection levels of these pollutants at contaminated sites. ,, This underscores the necessity of accounting for these cocontaminants when conducting bioremediation with Dehalococcoides . Interestingly, we also found that dechlorination of trans -DCE was more susceptible to cocontaminant inhibition compared to cis -DCE in the investigated Dehalococcoides -containing consortia, providing an alternative explanation for the more frequent detection of trans -DCE than cis -DCE at contamination sites .…”
Section: Discussionmentioning
confidence: 66%
“…Bioremediation employing Dehalococcoides populations capable of detoxifying chloroethenes has been widely applied to clean up relevant contamination sites. Field bioremediation efforts and laboratory investigations have indicated that cocontamination with other chlorinated solvents significantly affects the effectiveness of bioremediation for chloroethenes. , Despite the recognition of this issue for a long time, a comprehensive evaluation of the toxicity of environmentally relevant chlorinated cocontaminants on the metabolic activity of Dehalococcoides and other associated syntrophic microorganisms is lacking. The present study ranked chloroform as the most detrimental cocontaminant inhibiting microbial reductive dechlorination of DCEs by Dehalococcoides -containing consortia, followed by 1,1,1-TCA and 1,1,2-TCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation